Respuesta :

Answer:

The inverse of xy is yx.

Step-by-step explanation:

Given:  xy

We need to find the inverse of xy.

To find inverse of an expression, we need to replace the variable x by y and y  by x.

Given xy.

Now replace x by y and y by x, we get

yx

Therefore, the inverse of xy is yx.

Let me show you an example.

y = x - 2

To find the inverse function, replace x by y and y by x, we get

x = y - 2

It is an equation, to write the equation in terms of y, add 2 from both sides, we get

x + 2 = y -2 + 2

x + 2 = y

Therefore, y = x + 2